Does IFRS information on tax loss carryforwards and negative performance improve predictions of earnings and cash flows? - Sandra Dreher; Sebastian Eichfelder; Felix Noth (Journal of Business Economics, 2023)
We analyze the usefulness of accounting information on tax loss carryforwards and negative performance to predict earnings and cash flows. We use hand-collected information on tax loss carryforwards and corresponding deferred taxes from the International Financial Reporting Standards tax footnotes for listed firms from Germany. Our out-of-sample tests show that considering accounting information on tax loss carryforwards does not enhance performance forecasts and typically even worsens predictions. The most likely explanation is model overfitting. Besides, common forecasting approaches that deal with negative performance are prone to prediction errors. We provide a simple empirical specification to account for that problem.
Keywords: M40; M41; C53; 650; Performance forecast; Out-of-sample tests; Deferred tax assets; Tax loss carryforwards